C–H Activation: A Versatile Tool for the Synthesis of Niclosamide and Its Derivatives - Gundamalla, Rachel; Bantu, Rajashaker; Sridhar, B.; Reddy, B. V. Subba (Synlett, 2024)
A novel strategy has been developed for the direct and regioselective ortho-acetoxylation of N-(2-benzoylphenyl)benzamides through C–H activation using a catalytic amount of Pd(OAc)2 (5 mol%) and a stoichiometric amount of PhI(OAc)2 in a mixture of acetic anhydride and acetic acid. By using this protocol, a new series of niclosamide derivatives was produced in good yields. This is the first report on the synthesis of niclosamide and its derivatives by means of C–H functionalization. This newly developed method offers several advantages such as high regioselectivity, operational simplicity, and good to excellent yields. It provides a short three-step process for the synthesis of niclosamide involving acid–amine coupling, ortho-acetoxylation through C–H activation, and deacylation.
Keywords: C–H bond activation; transition-metal catalysis; acetoxylation; niclosamide